Pengaruh Kompetensi Kerja, Penempatan Kerja, dan Pemberian Insentif Terhadap Prestasi Kerja Pegawai pada PT XY - Adinda Nur Halizah Putri; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to determine how much influence work competence, job placement, and incentives have on employee performance at PT XY. The object of this research is employees who work at PT XY. The tool used for data collection in this study is a questionnaire with a Likert scale from point 1 to 5. This study uses non probability sampling technique by purposive sampling. The sample was taken as many as 100 respondents, namely employees who work at PT XY. The method used in this research is quantitative method with description analysis. The data analysis technique uses multiple linear regression analysis with the SMARTPLS 4 application through two sub models (outer model and inner model). Outer model consists of convergent validity, discriminant validity, averange variance extracted (AVE), and Cronbach's Alpha. While the inner model consists of model feasibility test, variance inflation factor (VIF), path coefficients, and total direct effect. Based on the results of the study, it can be concluded that work competence has a positive and significant effect on employee work performance, job placement has a positive and significant effect on employee work performance, and incentive.